Elastic and nonlinear crack tip solutions comparison with respect to failure probability (Fracture and Structural Integrity, 2022)
This study represents a methodology to assess the probability of failure based on three the driving force formulations defined by the corresponding brittle and ductile fracture criteria for compact and bending specimens made of 34XH3MA and S55C steels. The elastic stress intensity factor (SIF) and two types of the non-linear plastic SIFs were considered as the driving force or generalized parameter (GP) to determine the probability of failure assuming a three-parameter Weibull distribution. The elastic SIF were experimentally obtained for studied materials and specimen geometries whereas the plastic SIFs were numerically calculated for the same material properties, specimen configurations and loading conditions according to classical J2 and strain gradient plasticity theories. Different specimen types with varying relative crack lengths and thicknesses were investigated. Proposed the normalized generalized parameter accounting for brittle or ductile fracture can be used as a suitable failure variable that is confirmed by comparison of the obtained failure cumulative distribution functions based on the three studied GPs.
Keywords: Failure probability; Weibull distributions; Nonlinear stress intensity factors; Generalized parameters